Antimicrobial Photodynamic Inactivation Mediated by Tetracyclines in Vitro and in Vivo: Photochemical Mechanisms and Potentiation by Potassium Iodide. Issue 1 (December 2018) - Xuan, Weijun; He, Ya; Huang, Liyi; Huang, Ying-Ying; Bhayana, Brijesh; Xi, Liyan; Gelfand, Jeffrey; Hamblin, Michael
Abstract Tetracyclines (including demeclocycline, DMCT, or doxycycline, DOTC) represent a class of dual-action antibacterial compounds, which can act as antibiotics in the dark, and also as photosensitizers under illumination with blue or UVA light. It is known that tetracyclines are taken up inside bacterial cells where they bind to ribosomes. In the present study, we investigated the photochemical mechanism: Type 1 (hydroxyl radicals); Type 2 (singlet oxygen); or Type 3 (oxygen independent). Moreover, we asked whether addition of potassium iodide (KI) could potentiate the aPDI activity of tetracyclines. High concentrations of KI (200–400 mM) strongly potentiated (up to 5 logs of extra killing) light-mediated killing of Gram-negativeEscherichia coli or Gram-positive MRSA (although the latter was somewhat less susceptible). KI potentiation was still apparent after a washing step showing that the iodide could penetrate theE .coli cells where the tetracycline had bound. When cells were added to the tetracycline + KI mixture after light, killing was observed in the case ofE .coli showing formation of free molecular iodine. Addition of azide quenched the formation of iodine but not hydrogen peroxide. DMCT but not DOTC iodinated tyrosine. BothE .coli and MRSA could be killed by tetracyclines plus light in the absence of oxygen and this killing was not quenched by azide. A mouse model of a superficial wound infection caused by bioluminescentE .coli could be treated by topical application of DMCT and blue light and bacterial regrowth did not occur owing to the continued anti biotic activity of the tetracycline.